In Silico Investigation of the RBC Velocity Fluctuations in Ex Vivo Capillaries - Eren Çolak; Özgür Ekici; Şefik Evren Erdener (Applied Sciences, 2025)
A properly functioning capillary microcirculation is essential for sufficient oxygen and nutrient delivery to the central nervous system. The physical mechanisms governing the transport of red blood cells (RBCs) inside the narrow and irregularly shaped capillary lumen are complex, but understanding them is essential for identifying the root causes of neurological disorders like cerebral ischemia, Alzheimer’s disease, and other neurodegenerative conditions such as concussion and cognitive dysfunction in systemic inflammatory conditions. In this work, we conducted numerical simulations of three-dimensional capillary models, which were acquired ex vivo from a mouse retina, to characterize RBC transport. We show how the spatiotemporal velocity of the RBCs deviates in realistic capillaries and equivalent cylindrical tubes, as well as how this profile is affected by hematocrit and red cell distribution width (RDW). Our results show a previously unprecedented level of RBC velocity fluctuations in capillaries that depends on the geometric features of different confinement regions and a capillary circularity index <semantics>(Icc)</semantics> that represents luminal irregularity. This velocity fluctuation is aggravated by high hematocrit conditions, without any further effect on RDW. These results can provide a better understanding of the underlying mechanisms of pathologically high capillary transit time heterogeneity that results in microcirculatory dysfunction.